Underlying Trends and International Price Transmission of Agricultural Commodities - Atanu Ghoshray (Asian Development Bank (ADB), 2011)
This paper examines the extent to which increases in international food prices during the past few years have been transmitted to domestic prices in selected Asian developing countries. In analyzing the historical data, evidence on price transmission for important food commodities such as rice, wheat, and edible oil have been considered. The price transmission elasticity has been estimated using regression models coupled with recent econometric techniques such as unit root tests and error correction models with threshold adjustment. Finally, the paper draws some policy implications from the empirical results. This study provides the numerical estimates on the empirical relationship between international prices and domestic prices. The analysis uses commodity-specific monthly data rather than annual data during a period of substantial policy reforms in order to understand both long-run and short-run relationships between world and domestic prices.
hdl:11540/2028
Keywords: C22; Q11; 330; Global commodity crises; International food prices; Domestic food prices; Price transmission; Commodity price trends; Agricultural commodities; Agrarpreis; International; Lebensmittelpreis; Reis; Speisefett; Weizen; Welt